2019
DOI: 10.3390/su11143776
|View full text |Cite
|
Sign up to set email alerts
|

The Threshold Effect of China’s Financial Development on Green Total Factor Productivity

Abstract: Using the slacks-based measure (SBM) directional distance function and constructing the Luenberger productivity index, we measure the green total factor productivity (GTFP) of China’s provinces under resource and environmental restrictions. At the same time, based on the provincial panel data, the threshold regression method is used to empirically analyze the impact of financial development on green total factor productivity and its threshold effect. The study explores how technological innovation, foreign dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…They find that technological progress can significantly contribute toward GTFP development through existing environmental regulations. Zhou et al (2019) also measures Chinese provinces' GTFP and confirms how technological innovation affects it; they find that the effect of technological innovation on GTFP is nonlinear, with positive and increasing marginal efficiency. Chen, Lan, Gao, and Sun (2018) use a dynamic panel data model, and found that compared with technology introduction, independent research and development has a significant driving effect on GTFP.…”
Section: Literature Reviewmentioning
confidence: 95%
See 2 more Smart Citations
“…They find that technological progress can significantly contribute toward GTFP development through existing environmental regulations. Zhou et al (2019) also measures Chinese provinces' GTFP and confirms how technological innovation affects it; they find that the effect of technological innovation on GTFP is nonlinear, with positive and increasing marginal efficiency. Chen, Lan, Gao, and Sun (2018) use a dynamic panel data model, and found that compared with technology introduction, independent research and development has a significant driving effect on GTFP.…”
Section: Literature Reviewmentioning
confidence: 95%
“…Moreover, Xin and Qu (2019) analyze the impact of smart city policies on the GTFP in the context of urban development patterns; they also use the SBM index to calculate GTFP growth. Li and Liu (2017) use SBM to analyze the spatial pattern evolution of GTFP for 108 cities in the Yangtze River Economic Belt in 2003–2013, and Zhou et al (2019) estimate the GTFP of China's provinces under resource and environmental restrictions using the SBM DDF and Luenberger productivity index.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…are often measured by carbon emissions and will threaten human survival and development. Therefore, we should take environmental pollution into account to comprehensively measure the development of China’s agriculture [8].…”
Section: Introductionmentioning
confidence: 99%
“…Rahman and Salim [18] analyzed 6 main influencing factors of agricultural GTFP in Bangladesh. Moreover, fiscal decentralization, international policies and fiscal development are also major factors affecting GTFP [19][20][21]. However, there is still a lack of research on the driving factors of GTFP in the logistics industry.…”
Section: Introductionmentioning
confidence: 99%